Optimal Instrumentation: Adjustment and Hybridization of a Simulated Annealing Based Technique - Hernández, José Luis (2019)
This work presents an analysis on the behavior of a particular metaheuristic technique inspired by Simulated Annealing, SA, for the resolution of a problem of sensor network design in process plants, SNDP. This design problem is formulated as a combinatorial optimization problem and includes the selection and determination of the number of process variables that must be measured to achieve the specific state of knowledge about the plant. Different parametric configurations for the proposed heuristic are analyzed and discussed, as well as their performance in plants of increasing size and complexity.